External and internal influences yield similar memory effects: the role of deception and suggestion - Otgaar, Henry; Mangiulli, Ivan; Battista, Fabiana; Howe, Mark L. (Frontiers in Psychology, 2023)
In legal cases, testimonies can become contaminated because of an amalgam of external and internal influences on memory. It is well-established that external influences (e.g., suggestive interviews) can hurt memory. However, less focus has been placed on the impact of internal influences (e.g., lying) on memory. In the current review, we show that the available evidence suggests that both external and internal influences exert similar effects on memory. That is, we review studies showing that suggesting non-occurrences and suggesting non-experiences can lead to omission errors and false memories, respectively. Likewise, these memory effects are also observed when focusing on internal influences. That is, false denials, feigning amnesia and fabrication have been shown to affect memory in terms of forgetting (i.e., omissions) and false memories (i.e., commissions). Also, we show that both external and internal influences can lead to changes in the belief that an event occurred. We argue that in legal cases, triers of fact should concentrate on whether both types of influences might have affected testimonial accuracy in witnesses, victims, and suspects.